2015
DOI: 10.1002/2015gb005095
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial pyrogenic carbon export to fluvial ecosystems: Lessons learned from the White Nile watershed of East Africa

Abstract: Pyrogenic carbon (PyC) is important because of its role in the global organic C (OC) cycle and in modifying soil properties. However, our understanding of PyC movement from terrestrial to fluvial ecosystems is not robust. This study examined (i) whether erosion or subsurface transport was more important for PyC export from headwaters, (ii) whether PyC was exported preferentially to total OC (TOC), and (iii) whether the movement of PyC from terrestrial to aquatic ecosystems provides an explanation for the coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 64 publications
(112 reference statements)
1
24
1
Order By: Relevance
“…The leaching of PyC also depends on the particle size (dissolved vs. particulate form) and vegetation type. Slow leaching of PyC downward may be altered by the quality of PyC material left after the initial mass movement event and the post-fire vegetation recovery (Major et al, 2010;Kindler et al, 2011;Güereña et al, 2015). Leaching may be occurring in the depositional landform position, but we did not sample at depth into this landform position, as no pre-fire comparison samples exist for the deep soils in the depositional landform position.…”
Section: Downwards Mobilization Of Soc and Sommentioning
confidence: 99%
See 1 more Smart Citation
“…The leaching of PyC also depends on the particle size (dissolved vs. particulate form) and vegetation type. Slow leaching of PyC downward may be altered by the quality of PyC material left after the initial mass movement event and the post-fire vegetation recovery (Major et al, 2010;Kindler et al, 2011;Güereña et al, 2015). Leaching may be occurring in the depositional landform position, but we did not sample at depth into this landform position, as no pre-fire comparison samples exist for the deep soils in the depositional landform position.…”
Section: Downwards Mobilization Of Soc and Sommentioning
confidence: 99%
“…However, gaps remain in our understanding of the mechanisms through which erosional redistribution of PyC across fire-impacted landscapes can affect its stock and persistence in soil. So far, the relative rates of lateral and vertical transport of PyC, with erosion, leaching, and bioturbation, across differing landscapes remains largely unknown (Güereña et al, 2015;Rumpel et al, 2015). The erosion of PyC is also significant, because this loss from eroding hillslopes post-fire, as illustrated after the Gondola fire, can lead to differences in its apparent environmental persistence based upon topographic features of a landscape.…”
Section: Implications Of Post-fire Erosion For Long-term Persistence mentioning
confidence: 99%
“…Although, recent wildfire activity does not seem to have a significant effect on in-stream DBC Güereña et al, 2015;Wagner et al, 2015a), this material is continually exported from fire-impacted watersheds for decades after a burn event (Dittmar et al, 2012). This suggests that the aging of BC in soils may be a prerequisite to its dissolution and export to aquatic systems as DBC.…”
Section: Introductionmentioning
confidence: 99%
“…Soil regimes in these systems vary widely; for example, the Yenisei River watershed is underlain by every type of permafrost regime, causing the soil active layer depth to vary dramatically within high latitude watersheds (Kawahigashi et al, 2004). It has been suggested that subsoil transport is a primary mechanism for PyC export from terrestrial to aquatic systems (Güereña et al, 2015), which may be regulated by soilPyC associations. Czimczik and Masiello (2007) suggest that the ability of soil minerals to sorb PyC may be a main controller of PyC storage within soils, similar to bulk soil organic matter (SOM).…”
Section: Introductionmentioning
confidence: 99%